Argumentative Essay Patterns Produced by University Students - Siti Maria Ulfa; Oikurema Purwati (UNIB Press, 2023)
This study aims to discover patterns in students' argumentative essays in writing class. As is well known, argumentative writing in higher education has been difficult over the years, with students performing poorly compared to other papers required by the curriculum. A qualitative survey was conducted to obtain in-depth answers about students' argumentative essays, and the participants were 28 students. Still, only 12 essays were considered due to the quality of the writing itself. As a result, the students' argumentative writing results in three different looks. The first is that it was discovered that there was good surface structure but poor quality of reasoning; failure to rebut all of the counterarguments; good surface structure but the poor quality of reasoning, particularly with non-aligned rebuttals; good surface structure but poor rebutting undermining the overall quality of reasoning; and essays that conformed well to surface design because they contained two or three reasons. To summarize, students' knowledge of text content is determined by their ability to construct their thoughts based on false facts and, as a result, claim figures and invent experts in making their arguments. Therefore, students need instruction on what they are expected to accomplish in their writing.